Peran Guru dalam Mencengah Kenakalan Siswa SMA - Paramitha, Fadhilah; Siregar, Mhd.Fuad Zaini (Jurnal Pusat Studi Pendidikan Rakyat, 2024)
Education plays a strategic role as a long-term investment in nation building, preparing the younger generation with the necessary knowledge, skills and values. The National Education System Law emphasizes the importance of education in the holistic development of individuals. However, the education system is faced with various challenges, including equitable access to education, varying education quality, and the relevance of the curriculum to the needs of the world of work. This research uses descriptive qualitative methods to explore efforts to prevent juvenile delinquency in high schools. Through interviews with teachers and observations at school, this research found that communication between schools and parents as well as interpersonal communication between teachers and students have a crucial role in preventing juvenile delinquency. Prevention efforts are carried out by building good communication with parents, visiting the homes of students with problems, providing advice, guidance and direction to students, as well as developing students' social and emotional skills. The research results show that effective communication between schools and parents can produce positive changes in student behavior, reducing rates of truancy and withdrawal from school. Interpersonal communication between teachers and students plays an important role in helping students overcome personal and social problems, as well as building a harmonious relationship between teachers and students. Education has a crucial role in shaping individual character, knowledge and skills. Effective communication between schools and parents as well as between teachers and students is the key to preventing juvenile delinquency and improving the quality of education in schools.